2015
DOI: 10.1371/journal.pone.0143660
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking and Metabolic Health Biomarkers in Newborns

Abstract: BackgroundMaternal smoking has been associated with elevated risk of type 2 diabetes among the offspring in adulthood. The mechanisms underlying this fetal “programming” effect remain unclear. The present study sought to explore whether maternal smoking affects metabolic health biomarkers in fetuses/newborns.MethodsIn a prospective singleton pregnancy cohort (n = 248), we compared metabolic health biomarkers in the newborns of smoking and non-smoking mothers. Outcomes included cord plasma insulin, proinsulin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
5
17
0
1
Order By: Relevance
“…One study [10] found an association between prenatal smoking and higher IGF-1, although this was in a very small sample (n=62) without control for potential confounding variables. Also somewhat consistent with our results, in prior studies, prenatal smoking was not associated with IGF-2 [14, 22] and was inversely associated with IGFBP-3 [16, 22]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…One study [10] found an association between prenatal smoking and higher IGF-1, although this was in a very small sample (n=62) without control for potential confounding variables. Also somewhat consistent with our results, in prior studies, prenatal smoking was not associated with IGF-2 [14, 22] and was inversely associated with IGFBP-3 [16, 22]. …”
Section: Discussionsupporting
confidence: 93%
“…Most have shown an association between prenatal smoking and lower IGF-1 [11, 13, 14, 16, 22], consistent with our findings. One study [10] found an association between prenatal smoking and higher IGF-1, although this was in a very small sample (n=62) without control for potential confounding variables.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, maternal serum human placental lactogen, β-human chorionic gonadotropin, and placental growth hormone levels are negatively correlated with the number of cigarettes smoked per day [28] . Cord plasma concentrations of insulin-like growth factor-1 (IGF-1) and IGF-binding protein-3 were lower in fetuses of smoking mothers [29] . All these hormones interplay to ensure fetal growth; hence, any factor affecting the balanced cross talk may result in FGR through the increased risk of preterm labor and impaired placental function.…”
Section: Effect Of Smoking On the Maternal Multiorgan Systemmentioning
confidence: 99%
“…Stężenie adiponektyny w krwi pępowinowej noworodków matek chorych na cukrzycę, podobnie inne patologie ciąży, jak stan przedrzucawkowy, nie wpływają na stęże-nie adiponektyny u noworodka niezależnie od wystąpienia małej urodzeniowej mc [21]. Stosowanie diety śródziemnomorskiej oraz ilość spożywanej energii przez kobietę ciężarną, a także palenie papierosów w ciąży nie zmieniają istotnie stężenia adiponektyny w krwi pępowinowej noworodka [22,23]. Jedynymi dotychczas publikowanymi wynikami badań wpływu porodu zabiegowego (cięcie cesarskie planowe i nagłe) na stężenia adiponektyny u noworodków są badania Logana i wsp.…”
Section: Wstępunclassified